Rapid and Efficient Gene Editing for Direct Transplantation of Naive Murine Cas9+ T Cells - Majumder, Snigdha; Jugovic, Isabelle; Saul, Domenica; Bell, Luisa; Hundhausen, Nadine; Seal, Rishav; Beilhack, Andreas; Rosenwald, Andreas; Mougiakakos, Dimitrios; Berberich-Siebelt, Friederike (Frontiers in Immunology, 2021)
Gene editing of primary T cells is a difficult task. However, it is important for research and especially for clinical T-cell transfers. CRISPR/Cas9 is the most powerful gene-editing technique. It has to be applied to cells by either retroviral transduction or electroporation of ribonucleoprotein complexes. Only the latter is possible with resting T cells. Here, we make use of Cas9 transgenic mice and demonstrate nucleofection of pre-stimulated and, importantly, of naive CD3+ T cells with free guideRNA. This proved to be rapid and efficient with no need of further selection. In the mixture of Cas9+CD3+ T cells, CD4+ and CD8+ conventional as well as regulatory T cells were targeted concurrently. IL-7 supported survival and naivety in vitro, but T cells were also transplantable immediately after nucleofection and elicited their function like unprocessed T cells. Accordingly, metabolic reprogramming reached normal levels within days. In a major mismatch model of GvHD, only naive primary murine Cas9+CD3+ T cells altered their function in response to the knockout phenotype achieved by sole gRNA nucleofection. Not only ablation of NFATc1 or NFATc2, but also that of the NFAT-target gene IRF4 ameliorated GvHD. This emphasizes the necessity of gene-editing and transferring unstimulated human T cells during allogenic hematopoietic stem cell transplantation.